PENENTUAN KARAKTERISTIK GEOKIMIA BATUAN INDUK DAN PEMODELAN CEKUNGAN 1D SUMUR AFR -1 DI WILAYAH KERJA ONWJ - Raffiwan, Azka Fadhillah; Sutadiwiria, Yarra; Riyandhani , Cahyaningratri Prima; Anggarini, Kinanti Sayekti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2025)
The study area is located in the Offshore North West Java (ONWJ) Working Area, with research conducted on the AFR-1 well. Aims: to characterize the geochemical properties of source rocks and develop a 1D burial history model of the research area. The methodology: includes analysis of organic content through Total Organic Carbon (TOC), Rock-Eval pyrolysis, vitrinite reflectance, and heat flow measurements on samples. The primary source rock is identified within the Talang Akar Formation. Conclusion: The research results indicate that the source rock in Well AFR-1 has a TOC content ranging from 0.15% to 63.08%, with S1 and S2 values suggesting hydrocarbon generation potential. The hydrogen index (HI) and oxygen index (OI) reveal a dominance of Type II/III kerogen, indicating the ability to generate both oil and gas. Thermal maturity based on Tmax shows that the source rock has entered the oil and gas window. 1D basin modeling using geochemical data from Well AFR-1 demonstrates that the Talang Akar Formation, composed of shale, sandstone, and coal lithologies, can act as a source rock, with hydrocarbon expulsion in the Deltaic Talang Akar Formation beginning at 2.26 Ma (Pleistocene). This study provides deeper insights into the source rock potential and its implications for hydrocarbon exploration in the ONWJ (Offshore Northwest Java) working area.